Association between neuropsychological factors, cognitive processes and reading levels in children of different socioeconomic status Callao - Canales Gabriel, Ricardo (2013)
This research sought to contribute to the knowledge of the possible association between neuropsychological factors, cognitive processes and reading processes in children from two socioeconomic levels in Callao, Peru. We used a descriptive correlational design examining 60 children from private and public schools from medium/high socio-economic level (B) and low (E), with the child neuropsychological test Solovieva Quintanar, the WISC-IV (Wechsler intelligence test ) and reading Achievement Test PROLEC-R by Cuetos. Finally, we found association between various types of neuropsychological factors, cognitive processes and reading processes in examinated children, differential performance in cognitive processes and intelligence and process of reading for children from medium/high socioeconomic level (B).